Consumer Behavior in the Flour Market in European Union Countries - D.H.; Ya.S.; T.V. (Економіка, управління та адміністрування)
In the context of globalization and Ukraine’s European integration, the issue of entering the European market with value-added products becomes relevant for domestic enterprises. Uncertainty about consumption culture in EU countries, the peculiarities of wholesale and retail trade, and existing competition with Chinese manufacturers complicate market entry and the conquest of a certain niche. Agricultural and food enterprises also face problems with product certification and compliance with European food standards. At the same time, the high price of the final product and a large consumer market are positive conditions for expanding sales markets for domestic enterprises. This article presents an analysis of consumer behavior models for flour markets in the United Kingdom, Netherlands, and Poland. The analysis was based on trade balance indicators, import value, import prices, as well as the share of imports from individual countries. The article reveals the market characteristics of each of the mentioned countries: the peculiarities of flour market functioning and consumer preferences in the market. According to the conducted research, the United Kingdom has a high price compared to other countries ($0,74/kg) and high export potential until 2027 ($393,2 million). Consumers in the United Kingdom are looking for a diverse range of flour that can be used separately for bakery products, pizza, pasta, and cakes. The flour market in the Netherlands accounts for 4,8 % of global imports, has a negative trade balance ($101,6 million), and an export potential until 2027 of $917,9 million. In the Netherlands, 77 % of baking is done as a semi-finished product, and shock freezing is used in production. Poland has a high import growth (61 %) and a high import price ($0,62/kg). Polish consumers prefer organic and gluten-free products.